β-Cyclodextrin Modified Hydrogels of Kappa-Carrageenan for Methotrexate Delivery - Maria Nikitina; Nataliya Kochkina; Marianna Arinina; Valery Kulichikhin; Irina Terekhova (MDPI AG, 2023)
This work is aimed at developing a kappa-carrageenan (kCR) gel with increased methotrexate (MTX) content. β-Cyclodextrin (βCD), which is able to inclusion complex formation with MTX, has been used to increase the drug concentration in the hydrogel. The rheological behavior of the designed gels was investigated and the influence of MTX and βCD on the viscoelastic properties of kCR gel was studied in detail. The effect of βCD and its concentration on the MTX-releasing rate from the kCR gels was examined. The properties of kappa- and iota-carrageenans loaded with MTX were compared and the differences observed were explained in terms of different binding affinities of MTX to these polymers. The obtained gels provided desirable viscoelastic properties useful for topical application.